A survival analysis of the last great European plagues: The case of Nonantola (Northern Italy) in 1630. (2nd January 2019) - Alfani, Guido; Bonetti, Marco
Abstract : This paper develops the first survival analysis of a large-scale mortality crisis caused by plague. For the time-to-event analyses we used the Cox proportional hazards regression model. Our case study is the town of Nonantola during the 1630 plague, which was probably the worst to affect Italy since the Black Death. Individual risk of death did not depend on sex, grew with age (peaking at ages 40–60 and then declining), was not affected by socio-economic status, and was positively associated with household size. We discuss these findings in light of the historical–demographic and palaeo-demographic literature on medieval and early modern plagues. Our results are compatible with the debated idea that ancient plague was able to spread directly from human to human. Our methods could be replicated in other studies of European plagues to nuance and integrate the findings of recent palaeo-biological and palaeo-demographic research on plague.